Polska muzyka lutniowa na falach Polskiego Radia Lwów. Współpraca Marii Szczepańskiej i Adama Franciszka Eplera - Gurgul, Wojciech (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2023)
In 1937–1938 musicologist Maria Szczepańska and guitarist Adam Franciszek Epler presented on Polish Radio Lwów pioneering broadcasts connected with Polish lute music. Among them, the most important was the series of three transmissions under the title Profiles of Old Polish Lutenists (Sylwetki lutnistów staropolskich). During broadcasts works of lutenists associated with Poland were presented, e.g. compositions by Wojciech Długoraj, Diomedes Cato, Jakub Polak, Valentin Bakfark and Franciszek Maffon. In addition, Kazimierz Wajda, the famous actor from the Lwów’s Merry Wave (Wesoła Lwowska Fala), read poetry devoted to the lute. This article will present the details of broadcasts based on preserved documents: radio programs, press reports and materials of Maria Szczepańska from the archives of the Adam Mickiewicz University Library in Poznan and from the private archive of Barbara Epler-Matuchniak, Epler’s daughter. It will also show the place of programs in the history of Polish lute and guitar performance.